Do sentido de autenticidade a partir de uma confrontação com a possibilidade da finitude: interfaces de Heidegger e Frankl - Freitas, Aramis Welliton de (2024)
The theme of the dissertation is the meaning of authenticity in the confrontation with finitude, based on the possible dialog between Martin Heidegger's phenomenological-existential thought and Viktor Frankl's existential analysis. The problem investigated refers to the evidence of existential finitude and how this allows for the possibility of authenticity in existence, as these thinkers thematized in works such as Being and Time (1927) and The Doctor and the Soul: From Psychotherapy to Logotherapy (1945). The main objective of the research is to show, through the interpretation and analysis of the phenomenological thinking of these writers, how the sense of authenticity in report issues existence presents itself as a possibility of decision in the face of the imminence of the finitude of this existence. To this end, we sought to understand the concepts of Being-There, Being-in-the-world, Being-toward-Death, Anguish, property, and finitude, based on Heidegger's thought. Next, we sought to interpret the concepts of freedom of will, will to meaning, meaning of life, existential vacuum and responsibility, based on Frankl's thought. Subsequently, an analysis of the concepts researched was developed, with the aim of enabling understanding of how confrontation with the possibility of finitude can highlight the meaning of authenticity in existence, safeguarding the definition of the meaning of life and appropriation of the way of Being-in-the-World. We maintain that, faced with finitude, the human comes to know himself as a “Being-toward-Death”, unveiling, from this process, the call of consciousness for the appropriation of his own being, so that this human, as being -there, begin to exist in front of a project of meaning that guides your existence, bringing you closer to your existential condition and the care for the meaning of existing. The investigation now elaborated results from the researcher's interest, motivated by contact with lectures given by Heidegger and Frankl, in understanding how the phenomenon of authenticity in the face of the finiteness of existence can free the appropriation of one's own project of meaning of existence and relax and get in tune with the human being. with your most authentic way of being. In this way, we sought to study the topic, based on dialogue between these authors. The justification for this research is also academic because it considers the human need to find a meaning for existence, that is, to understand and decide on a meaning for their way of existing. Which, as researched, is linked to the confrontation with the possibility of the finiteness of existence. To fulfill its objectives, exploratory, qualitative research was developed, carried out using bibliographic methodology in the works of the thinkers, as well as in books, academic journals and specialized commentators, enabling immersion in the highlighted topic and learning from the knowledge developed by the authors.